An estimation of bactericidal properties of complex metallic disinfectant - Шкромада, О. І. (Scientific Progress & Innovations, 2012)
The data on research of bactericidal action of complex metallic disinfectant are given in article. Phenolic factor which expresses the relation of concentration of solutions of investigated substance to concentration of phenol that defines in an equal time interval at identical temperature equivalent temperature disinfectant effect was defined for this purpose. Albuminous index, an indicator of decrease in activity of a disinfectant in the presence of fiber was also defined. As a result of researches it is established that, bactericidal action complex metallic disinfectant is stronger than bactericidal action phenylic acid in 157,98 times. KMD can show bactericidal action on processed surfaces during contact with albuminous substances, but in that case its efficiency decreases in 2,92 times. That is considered at installation of effective concentration of working solutions KMD.